Global Relative Poverty - Nielsen, Lynge (IMF Working Papers; Working Paper ;, 2009)
The paper provides estimates of global relative poverty trends from 1970 onwards. Relative poverty is shown to have decreased significantly, but at the same time there has been a worsening poverty outcome among up to one billion of the world's poorest citizens. The paper also proposes a straightforward method for dividing an income distribution into classes of poor, rich, and middle-class.